Effector triggered immunity: Activation of innate immunity in metazoans by bacterial effectors - Rajamuthiah, Rajmohan (Landes Bioscience, 2014)
Pathogenic bacteria produce virulence factors called effectors, which are important components of the infection process. Effectors aid in pathogenesis by facilitating bacterial attachment, pathogen entry into or exit from the host cell, immunoevasion, and immunosuppression. Effectors also have the ability to subvert host cellular processes, such as hijacking cytoskeletal machinery or blocking protein translation. However, host cells possess an evolutionarily conserved innate immune response that can sense the pathogen through the activity of its effectors and mount a robust immune response. This “effector triggered immunity” (ETI) was first discovered in plants but recent evidence suggest that the process is also well conserved in metazoans. We will discuss salient points of the mechanism of ETI in metazoans from recent studies done in mammalian cells and invertebrate model hosts.